Analysis of the reaction and behavior of nurses after training on young child feeding - Ádria Marcela Vieira Ferreira; Leidiane Minervina Moraes de Sabino; Ludmila Alves do Nascimento; Jardeliny Corrêa da Penha; Lorena Pinheiro Barbosa; Francisca Elisângela Teixeira Lima; Regina Cláudia Melo Dodt; Mariana Cavalcante Martins
ABSTRACT Objective: to assess the reaction and behavior of nurses after training on the use of educational tool to promote heathy nutrition to children. Method: pilot assessment study, of descriptive and quantitative approach, carried out in 2014 with eight nurses from the rural area of Ceará, Brazil, by observing a training workshop on the use of the serial album "Alimentos regionais: promovendo a segurança alimentar na promoção da alimentação infantil saudável" [Regional food: promoting food safety through child healthy feeding]. Results: the analysis of the reaction of nurses to the workshop showed that all of them (100%) were satisfied with the training. In behavior analysis, more than a half of the nurses have achieved the expected performance when implementing the illustrations of the serial album, seven of them (87.5%) being considered able to use the serial album. Conclusion: the training was considered effective, as all the participant nurses were satisfied and most of them considered capable of using the educational tool in promoting child healthy feeding.